Podążając śladem dziecięcego rozumienia świata społecznego. Uwagi na marginesie badań mozaikowych - Agnieszka Nowak-Łojewska (Problemy Wczesnej Edukacji)
The text is about social education of children and it presents an approach related to a new paradigm of a child and childhood as well as solutions drawing on constructivism. It highlights the sense of children’s exploration and their active participation in creating knowledge about themselves, others and their social background. The methods used comprise mosaic approach, tours, map-making, using cameras, child conferencing. These methods emphasize a child as an explorer and their active participation in learning new skills and gaining new knowledge. The main idea of the text is, therefore, to show the mosaic research strategy as a chance for professional implementation and achievement of research goals related to learning about the world of children, as well as creating opportunities for attractive and valuable learning about the world by children when they explore their surroundings. This kind of the meeting of two perspectives of a mosaic strategy: methodological as a research method and methodological as a learning method has its potential and interesting perspectives of multilateral application.